Gambaran Tingkat Pengetahuan Dan Sikap Ibu Tentang Deteksi Dini Kanker Payudara Di Yayasan Kanker Indonesia Cabang Kalimantan Selatan Tahun 2014 - Nina Rahmadiliyani; Tri Handayani; Eva Rahmawati; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2015)
Background : Cancer constitutes disease that really been discouraged society because frequent causes death. Breast cancer happens since be troubled sistem cell growth at deep breast network. To the effect : Knowing mother’s knowladge and attitude about early detection of breast cancer at Indonesian Cancer Foundation, South Kalimantan’s branch. 2014. Observational method : This research utilize descriptive method. Research is done April May 2014. Population are exhaustive mother about cancer early detection breast as much 70 person and sample that taking to utilize accidental is sampling . Observational instrument by use of kuesioner. Analysis did by analisis's data univariat's ala. Observational result: knowladge Level description and mother attitude about cancers early detection breast as much 70 mother that do early detection of breast cancer which is available 29 respondents (41,42%) with enough knowledge, 25 respondents (35,72%) with good knowledge, 16 respondents (22,86%) with subtracted knowledge. Meanwhile mother attitude to early detection of breast cancer available 45 respondents (64,28%) with positive attitude, and 25 respondents (35,72%) with negative attitude.